2019
DOI: 10.1111/bjso.12325
|View full text |Cite
|
Sign up to set email alerts
|

Television exposure, consumer culture values, and lower well‐being among preadolescent children: The mediating role of consumer‐focused coping strategies

Abstract: Previous research has linked materialism to lower well‐being in children, and recent findings suggest that this link is heightened among those exposed to high levels of advertising. One proposal is that children may be pursuing consumer culture ideals (CCIs) – orienting to material possessions and physical appearance – as a maladaptive coping strategy for dealing with underlying distress. The present work offers the first direct evaluation of this theoretically plausible hypothesis. In Study 1, higher scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…In 43 samples from 40 studies (99 603 children), the effect size between child screen time and internalizing problems was weak but significant ( r , 0.07; 95% CI, 0.05-0.08) (Figure 3). The funnel plot showed some asymmetry (eFigure 2 in the Supplement), indicating possible publication bias; however, the Egger test result did not suggest that smaller sample sizes had more extreme effect sizes. The Q statistic was significant ( Q , 285.10; P < .001; I 2 , 85.27), and moderator analyses were conducted to explain between-study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 43 samples from 40 studies (99 603 children), the effect size between child screen time and internalizing problems was weak but significant ( r , 0.07; 95% CI, 0.05-0.08) (Figure 3). The funnel plot showed some asymmetry (eFigure 2 in the Supplement), indicating possible publication bias; however, the Egger test result did not suggest that smaller sample sizes had more extreme effect sizes. The Q statistic was significant ( Q , 285.10; P < .001; I 2 , 85.27), and moderator analyses were conducted to explain between-study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 95%
“…Dunkeld et al,121 2020, sample 2 Erdogan et al, 56 2006 Guerrero et al, 43 2019 Guxens et al, 60 2019 Hosokawa et al, 66 2018 Kahn et al, 69 2020 Lam et al, 122 2019 Lin et al, 73 2020 Lin et al, 123 2020 Liu et al, 42 2016 Lobel et al, 74 2017 Martin et al, 76 2012 McNeill et al, 78 2019 Mistry et al, 81 2007 Mundy et al, 83 2017 Neville et al, 16 2021 Niiranen et al, 84 2021 Özmert et al, 87 2002 Parkes et al, 88 2013 Poulain et al, 92 2018 Rosen et al, 94 2014 Sanders et al, 95 2016, older children Sanders et al, 95 2016, younger children Séguin et al, 98 2016 Stenseng et al, 101 2020 Tamana et al, 105 2019 Tansriratanawong et al, 106 2017 Teramoto et al, 107 2005 Wan et al, 110 2021 Wu et al, 113 2016 Wu et al, 114 2017 Xie et al, 115 2020 Yousef et al, 116 2014 Zhang et al, 124 2020 Zhu et al, 125 2019 Heterogeneity: Q = 285.10; P <.001; I 2 = 85.27…”
mentioning
confidence: 99%
“…Fifteen years ago, a large-scale literature review (Buijzen & Valkenburg, 2003a) highlighted a consistently positive correlation between exposure to TV advertising and youth materialism concluding that “analysis clearly suggests that exposure to advertising stimulates materialistic values in children” (p. 451). Work since then has reinforced this finding (e.g., Dunkeld et al, 2019; Goldberg et al, 2003; Schor, 2004), and at the same time, longitudinal and experimental studies, past and present, have supported the hypothesis that advertising exposure leads to materialism rather than the alternative proposition that materialistic children seek out adverts to inform their compulsion to purchase.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 93%
“…Policymakers and consumer advocacy groups should pay specific attention to children. Research has shown that children's exposure to materialistic messages is associated with materialism (Buijzen & Valkenburg, 2003; Dunkeld et al, 2020). In today's world, children are exposed to an enormous amount of marketing messages both on traditional and social media.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%